The preimaginal stages of the ensign wasp Evania appendigaster (Hymenoptera, Evaniidae), a cockroach egg predator - Paterson Fox, Eduardo Goncalves; Solis, Daniel Russ; Rossi, Monica Lanzoni; Eizemberg, Roberto; Taveira, Luiz Pilize; Bressan-Nascimento, Suzete (Wiley-Blackwell, 2012)
Evania appendigaster is a cosmopolitan wasp that deposits eggs in the oothecae of some species of cockroaches; its larvae then consume the cockroach eggs and embryos. It is a candidate for the biological control of cockroaches, but little is known about its basic biology. Here we describe the external morphology of all immature stages of E. appendigaster and compare them with the larvae of related species. The life cycle of E. appendigaster includes three larval instars, each with 13 body segments. Their mouthparts were generally reduced, except for the mandibles, which were always sclerotized and toothed, and were especially robust in second-instar larvae. Antennal and mouthpart sensilla were basiconic and difficult to observe. Larvae of E. appendigaster are similar in form to other described evaniid larvae, but quite different from the two available descriptions of larvae of gasteruptiid and aulacid wasps. Further descriptions of evaniid larvae will be useful in determining how widespread this morphology is within the family, and in understanding phylogenetic relationships within Hymenoptera.
Keywords: larval morphology; instar; Periplaneta americana